The unique role of cardiovascular magnetic resonance imaging in acute myocarditis - Chetrit, Michael; Friedrich, Matthias (F1000Research, 2018)
This article addresses the specific diagnostic information provided by cardiovascular magnetic resonance (CMR) in patients with suspected acute myocarditis. It gives an overview of the current evidence of the ability of CMR to detect myocardial inflammation and discusses the added value as well as its limitations in clinical settings. Because of the large variety of symptoms and the limited specificity of other non-invasive procedures, the identification of myocardial inflammation is of paramount importance. Because of its accuracy in imaging ventricular volumes and function and its unique ability to visualize myocardial edema, scar, and other tissue abnormalities, CMR has emerged as the prime non-invasive diagnostic tool in patients with acute myocarditis. The presence of myocardial inflammation is not specific to viral myocarditis or other forms of acute myocardial injury, and the regional distribution within the myocardium helps differentiate acute myocarditis from other diseases. The currently recommended diagnostic criteria (Lake Louise Criteria) include markers for hyperemia/capillary leak, edema, and inflammatory scarring. Their diagnostic accuracy of close to 80% is satisfactory to rule in myocarditis, yet the negative predictive value is less than 70%. Novel CMR techniques, especially T1 and T2 mapping, have been shown to further improve the diagnostic utility.
First published: 30 Jul 2018, latest published: 30 Jul 2018, last updated 15 Aug 2018
Gesehen am 24.04.2019